(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To investigate the sources promoting use of disposable diapers, and document reasons and frequency of disposable diapers use. Design: Descriptive study. Place and Duration of study: The study was conducted in the Department of Social & Preventive Pediatrics, Fatima Jinnah Medical College, Sir Ganga Ram Hospital from January to May 2010. Material & Methods: Four hundred and sixty mothers with babies under 24 months of age were enrolled in the OPD of the Dept. of Social and Preventive Pediatrics, FJMC/SGRH after getting informed consent. The information was collected using a predesigned, pretested, questionnaire. Results: The group consisted of 254 males and 206 females. The average age of babies was 6 months. 412 (90%) mothers used disposable diapers (DD) at times for their babies. 144 (35%) mothers were motivated by television adds , 127 (31%) by family members, 108 (26%) inspired by other miscellaneous sources and only 33(8%) used on advice of gynecologists and pediatricians. Conclusion: The media played a dominant role by projecting advertisements demonstrating benefits of disposable diapers and quoting it as recommended by doctors.